A Novel Technique for the Bedside Reduction of the Posterior Hip Dislocation. Issue 3 (September 2017) - Ayzenberg, Mark; Arango, Dillon; Clippinger, Benjamin; Saing, Minn
Abstract : The dislocated hip is a common condition seen in the emergency room and requires urgent reduction, especially in the case of the native hip, which carries a high risk of a vascular necrosis with increasing time to reduction. There are several reduction techniques described in the literature, the Allis technique being the among the more common methods utilized by orthopedic surgeons. This technique requires multiple assistants, applies significant force about the knee, and places the physician at risk for back strains and even falling off the gurney during the reduction maneuver. We describe a case of a historically irreducible recurrent total hip dislocation successfully relocated in the emergency room utilizing a novel technique that offers several advantages over the standard reduction method.